2007
DOI: 10.1016/j.rmed.2007.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Residential proximity fine particles related to allergic sensitisation and asthma in primary school children

Abstract: Findings support the hypothesis that changes in allergy prevalence observed in recent decades might be partly related to interactions between traffic-related air pollution and allergens. Further longitudinal investigations are needed to corroborate such results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(108 citation statements)
references
References 37 publications
6
101
0
1
Order By: Relevance
“…This might be another reason for the higher prevalence of asthma in urban areas compared to rural areas. Traffic-related air pollution may possibly increase the risk of allergy development and may exacerbate symptoms in particular in susceptible subgroups [53][54][55][56]. Although traffic-related air pollution levels are usually higher in urban areas, it is not necessarily the case for outdoor industrial air pollution levels or indoor air pollution levels from polluting fuels used for cooking or heating.…”
Section: Discussionmentioning
confidence: 99%
“…This might be another reason for the higher prevalence of asthma in urban areas compared to rural areas. Traffic-related air pollution may possibly increase the risk of allergy development and may exacerbate symptoms in particular in susceptible subgroups [53][54][55][56]. Although traffic-related air pollution levels are usually higher in urban areas, it is not necessarily the case for outdoor industrial air pollution levels or indoor air pollution levels from polluting fuels used for cooking or heating.…”
Section: Discussionmentioning
confidence: 99%
“…Gold et al 1999;Lee et al 2002;John et al 2007;Annesi-Maesano et al 2007;Oravisjarvi et al 2008). These studies demonstrated that indoor PM levels are greatly affected by the presence of pupils and the intensity of their indoor activities, as well as outdoor PM levels.…”
Section: Background Aim and Scopementioning
confidence: 99%
“…Estudos têm reportado associações entre a proximidade de residências a rodovias e indústrias e desfechos respiratórios em crianças, incluindo sintomas como sibilância e exacerbação de asma [7][8][9] . Smargiassi et al 8 relataram episódios de elevação dos níveis de dióxido de enxofre (SO 2 ) liberados por uma refinaria no Canadá, associados com o aumento de episódios de asma em crianças residentes no entorno.…”
Section: Introductionunclassified